Growth Hormone Releaser Attenuates β-Amyloid (1 - 42)-Induced Memory Impairment in Mice - Eun-Joo Shin; Jin Hyeong Jhoo; Toshitaka Nabeshima; Wang-Kee Jhoo; Myung Sang Kwon; Yong Kwang Lim; Jong Seok Chae; Myung Eun Jung; Seok Joo Park; Kyung Jin Jang; Hyoung-Chun Kim (Elsevier, 2005)
Accumulating evidence indicates that growth hormone (GH) might be effective at preventing the development of Alzheimer's disease. However, exogenous GH treatment has exhibited side effects for clinical application; thus supplementation with amino acids to promote the release of GH could be a possible alternative treatment. In this study, mice that were fed with a diet of GH-releasing supplements had significantly attenuated memory impairments and hippocampal changes in the acetylcholinesterase activity and acetylcholine level induced by amyloid beta protein (Aβ) (1 - 42). Our results suggest that the use of GH-releasing supplement exerts beneficial effects on the memory impairment induced by Aβ (1 - 42). Keywords:: growth hormone releaser, amyloid beta protein, cognitive enhancer